Development of a new tuberculosis vaccine: is there value in the mucosal approach?. (September 2014) - Diogo, Gil Reynolds; Reljic, Rajko
TB is a global health problem, killing 1.5 million people every year. The only currently available vaccine, Mycobacterium bovis BCG, is effective against severe childhood forms, but it demonstrates a variable efficacy against the pulmonary form of TB in adults. Many of these adult TB cases result from the reactivation of an initially controlled, latent Mycobacterium tuberculosis infection. Effective prophylactic vaccination remains the key long-term strategy for combating TB. Continued belief in reaching this goal requires unrelenting innovation in the formulation and delivery of candidate vaccines. It is also based on the assumption, that the failure of recent human vaccine trials could have been due to a suboptimal vaccine design and delivery, and therefore should not erode the key principle that a TB vaccine is an attainable target. This report gives a brief overview of the mucosal immune system in the context of M. tuberculosis infection, and focuses on the most recent advances in the field of mucosal TB vaccine development, with a specific emphasis on subunit TB vaccines.